Cover Image, Volume 15, Issue 1. (27th February 2017) - Treggiari, E.; Ressel, L.; Polton, G. A.; Benoit, J.; Desmas, I.; Blackwood, L.
Abstract : The cover image, by E. Treggiari et al., is based on the Original Article Clinical outcome, PDGFRß and KIT expression in feline histiocytic disorders: a multicentre study, DOI:10.1111/vco.12142 . Abstract : The cover image, by E. Treggiari et al., is based on the Original Article Clinical outcome, PDGFRß and KIT expression in feline histiocytic disorders: a multicentre study, DOI:10.1111/vco.12142 .